Reverse engineering injury mechanism - Charniga, A. (EWF Scientific Magazine, 2016)
Reverse engineering can help explain the extremely low rate of ankle injury in weightlifting and why weightlifters who have fallen or otherwise experienced a "black swan" event without injury. The following theory appears to fit. Weightlifters have to switch instantaneously from raising a barbell to receiving it on the chest or over-head on straight arms. In effect, it is analogous to switching from throwing a heavy object to instantaneously catching it. The weightlifter "throws" the barbell by forcefully straightening the trunk and lower extremities; in the process stiffening the leg spring, i.e., the muscles, tendons and ligaments from the hip to foot. The weightlifter has to relax the very same muscles used to straighten up in order to switch to dropping down. Tension is released in the leg spring. A lifter can suddenly experience some problem with balance or coordination in the process of receiving the barbell. The tension which has returned to the leg spring once the athlete's feet return to the platform in the process of descending can be released (as in the examples shown) such that the mechanical energy of the athlete's descending body and the barbell can be redistributed and/or otherwise dissipated; preventing injury.The high speed relaxation of the leg spring, both a skill and a special quality cultivated by the high class weightlifter, to switch from lifting to receiving the barbell becomes a reactive protective mechanism. The release of tension coupled with the weightlifter's flexibility prevent injury. The ability to release tension in the leg spring extremely fast allows a highly skilled weightlifter's body to exceed the acceleration of gravity while dropping into a low squat. Soviet sport scientist I. Zhekov (1976), theorized the possibility of a weightlifter dropping under a barbell with an acceleration of 2Gs. However, it is only possible to outstrip the acceleration of a free falling body by holding onto something, which in this case is the very slow moving barbell.